The black hole information paradox - Landulfo, André G. S. (Cadernos de Astronomia, 2025)
In 1974, a discovery shook the scientific community. Stephen Hawking showed that, when quantum mechanics is taken into account, black holes are not black but emit thermal radiation, as measured by stationary observers far away from the black hole. Since then, the resulting process of black hole evaporation has sparked a debate that divides physicists to this day: what happens to the information that falls into the black hole? In this article, we will review the process of black hole evaporation, showing in particular that there is nothing paradoxical about the loss of information in the end. We will then examine the alternatives to information loss, highlighting their pros and cons.